The Effect of Inflation Perception, Interest Rate, Investment Knowledge and Risk, On Customer Decisions to Invest in Bank BTN Manado Branch Office - Restu Kurniawan; Vecky AJ Masinambow; Tri Oldy Rotinsulu (International Journal on Economics, Finance and Sustainable Development, 2022)
In 2014 Bank BTN opened its priority outlet in Manado City, North Sulawesi. For approximately 6 years, the Manado Branch Priority Outlet managed to raise funds with a total under management of IDR 189 billion consisting of several investment products. With a total of 325 customers, BTN Prioritas is here to facilitate customers in terms of wealth management with savings products, deposits, bonds, mutual funds, and bancassurance. The purpose of this study is to see how much influence several factors have on making investment decisions for priority customers at Bank BTN Manado Branch Office. There are 4 independent variables in this study, namely risk perception, interest rate perception, investment knowledge, and risk perception. And one dependent variable, namely investment decisions. This study uses primary data, and the population used is priority customers of Bank BTN Manado Branch Office who have managed funds of more than or equal to five hundred million rupiah. The data collection technique in this study used a questionnaire with the Likert scale method to measure customer perceptions of each independent variable. The analytical method used in this study uses multiple linear regression analysis.